Hilirisasi Nikel sebagai Nilai Tambah dalam Penguatan Perekonomian Indonesia - Auderey G. Tangkudung; Jemmi Y. Kaseger (Jurnal Syntax Admiration, 2024)
In addition to nickel used for export, the government currently requires the downstreaming of nickel in the country. In addition, the potential of nickel in Indonesia also plays a role in increasing state revenue investment, through smelter investment. Through the nickel export ban policy, the long-term continuity of raw nickel supply for domestic smelter needs is maintained. However, there are problems in the community due to the export ban that affects the selling price of nickel, especially affecting business activities. This paper discusses the extent of nickel downstream policies, the ban on nickel ore exports, the added value obtained and the obstacles faced. The research methods used are exploratory and descriptive methods, data collection for analysis purposes is obtained from various literature, regulations and legislation, media reports and various other relevant secondary data sources. The findings show that nickel downstreaming actually creates an additional impact on the nickel industry. value and pushing nickel prices in a positive direction so as to encourage investors to come to Indonesia so as to strengthen Indonesia's economy in a better direction.